Carcinoma Buccal Mucosa Presenting as Ocular Metastasis to the Choroid - Jyoti, Poddar; Ashutosh, Sharma; Maitrik, J Mehta; Ubrangala, Kunikullaya Suryanarayana (Indian Journal of Medical and Paediatric Oncology, 2018)
Metastasis to eyes from a head and neck carcinoma is a rare event. A 62-year-old male presented with carcinoma of the left buccal mucosa. The patient was operated and was pathological stage pT2N0Mx. The patient was advised adjuvant postoperative radiotherapy (60Gray/30#). During the treatment, he presented with progressive diminution of vision in the left eye. He was investigated and was found to have choroidal secondaries in the left eye involving 80% of the globe. On positron emission tomography-computed tomography scan, no metastatic lesion was found elsewhere in the body. Ocular metastasis in a case of T2NOMx without pulmonary metastasis is a rare event.
Keywords: Carcinoma buccal mucosa; choroidal metastasis; distant metastasis; secondaries in eyes